1991
DOI: 10.1128/aac.35.6.1070
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that amikacin ototoxicity is related to total perilymph area under the concentration-time curve regardless of concentration

Abstract: Previous studies have failed to fully establish whether ototoxicity is related in any way to the levels of an aminoglycoside antibiotic in the perilymph. To study this we exposed guinea pigs to continuously infused amikacin at four different dosing rates under conditions parallel to those used in our previous study which related ototoxicity to total plasma area under the concentration-time curve regardless of the level in plasma. It was found that at all dosing rates, levels in the perilymph and ratios of leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 21 publications
3
18
0
1
Order By: Relevance
“…The auditory toxicity is associated with the concentration of AG in the inner ear (14). In this study, low-dose LPS injection was shown to enhance the accumulation of GTTR in cochlear but not in serum, which is congruent with the earlier finding that the ototoxicity was independent of plasma AG concentration (7).…”
supporting
confidence: 90%
“…The auditory toxicity is associated with the concentration of AG in the inner ear (14). In this study, low-dose LPS injection was shown to enhance the accumulation of GTTR in cochlear but not in serum, which is congruent with the earlier finding that the ototoxicity was independent of plasma AG concentration (7).…”
supporting
confidence: 90%
“…The degree of aminoglycoside-induced hair cell death appears to be dependent on the degree of intracellular drug uptake, and both decrease along a baso-apical gradient in the cochlea (Beaubien et al, 1991;Hackney et al, 1990;Hiel et al, 1992a;Hiel et al, 1992b). Physiologically, the cationic aminoglycosides reversibly abolish the transduction current in hair cells, and are permeant blockers of the transduction channels (Kroese et al, 1989;Marcotti et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…An animal study showed that concentration and duration of amikacin may cause HL by increasing perilymph amikacin levels. 13 The duration and dose of the amikacin have been suggested to influence toxicity. 14 A previous study however showed that aminoglycoside treatment for >5 days in the NICU was associated with HL in univariable, but not in multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%